Decolonizing wealth : indigenous wisdom to heal divides and restore balance - Villanueva, Edgar; Barber, William J., II, 1963- (Oakland, CA : Berrett-Koehler Publishers, 2021)
"This second edition expands the provocative analysis of the dysfunctional colonial dynamics at play in philanthropy and finance into other sectors and offers practical advice on how anyone can be a decolonizer"--
Part one. Where it hurts -- Stolen and sold -- Arriving at the plantation -- House slaves -- Field hands -- The overseers -- Freedom -- Part two. Being a healer -- Medicine beyond money -- Story as medicine -- Part three. How to heal -- Grieve -- Apologize -- Listen -- Relate -- Represent -- Invest -- Repair.
Includes bibliographical references and index.
Keywords: Income distribution -- United States; Wealth -- United States; Unjust enrichment -- United States; Restitution -- United States; Indians of North America -- United States; Slavery -- United States; Postcolonialism -- United States